Restorying the Experiences of Muslim Women Academics in Indonesian State Islamic Higher Education: A Narrative Inquiry - Siti Muflichah (Centre for Asian Social Science Research (CASSR), Faculty of Social and Political Sciences, UIN Sunan Gunung Djati Bandung, 2020)
In the last three decades, women have been the majority of undergraduate students in Indonesian higher education. However, the story is different when it comes to women as academics in Islamic higher education institutions. Compared to their male colleagues, female academics have unequal academic and lower leadership positions. There is a low percentage of female academics who have achieved the academic positions of associate professors or professors. They also have low productivity in research and publications. This article deals with the inequality facing Muslim women academics in Indonesian state Islamic higher education (Perguruan Tinggi Keagamaan Islam Negeri [PTKIN]). It asks the question: Do these problems happen due to no opportunities given to Muslim women academics to develop their academic career? In doing so, this article uses narrative inquiry as an approach to revealing the story of Indonesian Muslim academics and the voice of Muslim feminists, which is not internationally acknowledged and recognized. It focuses its analysis on the voice and career experiences of a Muslim woman (Muslimah) academic in an Indonesian state Islamic university using the feminist methodology. It aims to portray how and why female academics face unequal academic achievement. Understanding their voice of higher academic promotion is important to solve the problem of the ‘leaking pipeline’ about genderbased representation in university. The article argues that Indonesian Muslimah academics had low representation at academic advancement as they experienced more barriers than their male colleagues.